Synthetic method and application of defective metal organic framework catalyst
By introducing ferrocene formic acid as a defect regulator in the metal organic frame catalyst, changing the coordination environment and electronic configuration of the metal nodes, the problems of low catalytic activity and poor thermal stability of the existing catalysts are solved, and efficient oxygen precipitation reaction is achieved and cost-reducing effects.
Patent Information
- Application Number
- CN202411622999.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
AI Technical Summary
The existing metal organic framework catalysts have low catalytic activity in oxygen precipitation reaction (OER), and the framework is prone to collapse during high-temperature calcination, which limits its application.
By introducing ferrocene formic acid as a defect regulator, the coordination environment and electronic configuration of the metal nodes are changed, and the defective metal organic framework catalyst is synthesized by hydrothermal method.
The catalytic activity of the oxygen precipitation reaction (OER) is significantly improved, the cost of use is reduced, and the thermal stability of the catalyst is maintained.
Smart Images

Figure CN119465249A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of organic framework catalysts, and specifically relates to a synthesis method of a defective metal organic framework catalyst and application thereof. Background Art
[0002] Developing efficient electrochemical conversion methods has always been an effective way to solve the storage and utilization of renewable energy. Among them, the oxygen evolution reaction (OER) plays a vital role in energy conversion technologies such as metal-air batteries, water splitting, and carbon dioxide reduction. However, the efficiency of OER is limited by sluggish reaction kinetics and high overpotential. Therefore, there is an urgent need to develop efficient OER electrocatalysts. Although precious metal-based RuO 2 and IrO 2 The OER electrocatalysts with high catalytic activity and stability have attracted much attention in recent years.
[0003] Metal-organic framework compounds (MOFs), as a new type of crystalline material, have gradually attracted attention in the field of OER catalysis due to their large specific surface area, adjustable pore size and diversity of metal nodes. Existing studies have shown that porous carbon nanocomposites prepared by calcining MOF as a precursor have extremely high catalytic activity. However, the high temperature conditions required for calcination often lead to the collapse of the MOF skeleton, and an inert gas or reducing gas atmosphere is also required, which greatly limits the practical application of MOF. Therefore, directly using MOF as an electrocatalyst is the best solution. However, most MOF materials have poor electrical conductivity and electrocatalytic activity, although there are some methods, such as metal node engineering, hydroxide ligand coordination and lattice strain, which can regulate the electrocatalytic activity of MOF. However, the direct use of MOF as an OER electrocatalyst is still in its infancy, and there are still huge challenges to further improve the electrocatalytic activity of such materials.
[0004] The electrocatalytic performance of solid materials is mainly reflected in the number of active sites, electronic conductivity and reaction energy barrier of the catalyst. In addition to adjusting the morphology and crystal structure of the catalyst, optimizing the electronic structure of the catalytic active site is the most direct way to change the inherent properties of the catalyst (such as electronic conductivity and reaction energy barrier). The electronic structure of the metal node of MOF is mainly affected by the topological structure and coordination environment. Due to the high design flexibility of MOF, non-bridging ligands (defect modifiers) can be used to partially replace the bridging ligands to change the coordination environment of the metal node, thereby controllably introducing defects into the MOF matrix. Therefore, integrating functional defect modifiers into the MOF matrix can effectively modulate the electronic structure of the MOF active site, which provides a new opportunity to improve the electrocatalytic performance of MOF. . Summary of the invention
[0005] In order to effectively improve the OER electrocatalytic activity and reduce the cost of use, the present invention proposes a method for synthesizing a defective metal organic framework catalyst. The present invention adopts a defect engineering strategy commonly used in solid materials to modify the MOF electrocatalyst, and creates defect sites by introducing ferrocenecarboxylic acid as a defect modifier into the NiBDC material. The defect modifier can achieve controllable regulation of the electronic configuration by changing the coordination environment of the metal node, thereby achieving the purpose of improving the electrocatalytic activity. .
[0006] A method for synthesizing defective metal organic framework catalysts is to synthesize nickel nitrate hexahydrate (Ni(NO 3 ) 2 6H 2 O) reacts with an organic ligand and a defect modifier to obtain a defective metal organic framework catalyst (defective nickel-based MOF catalyst); the defect modifier is ferrocenecarboxylic acid, and the organic ligand is terephthalic acid (H 2 BDC).
[0007] Preferably, the molar ratio of the organic ligand to the defect modifier is 1:(0.1-1).
[0008] Preferably, a method for synthesizing a defective metal organic framework catalyst comprises the following steps:
[0009] Step 1), dissolving terephthalic acid and ferrocenecarboxylic acid in N,N-dimethylformamide, and adding NaOH solution dropwise to obtain solution A; the molar ratio of terephthalic acid to ferrocenecarboxylic acid is 1:(0.1-1);
[0010] Step 2), dissolving nickel nitrate hexahydrate in N,N-dimethylformamide to obtain solution B;
[0011] Step 3), solution A and solution B are mixed evenly, added into a stainless steel autoclave, heated for a period of time, and then the obtained product is washed and dried to obtain a defective metal organic framework catalyst.
[0012] Preferably, step 1) is specifically as follows: dissolving terephthalic acid and ferrocenecarboxylic acid in 5 mL of N,N-dimethylformamide, and adding 1 mL of 0.4 M NaOH dropwise thereto to obtain solution A; the terephthalic acid is 1 mmol;
[0013] Preferably, step 2) is specifically as follows: dissolving 1 mmol of nickel nitrate hexahydrate in 5 mL of N,N-dimethylformamide to obtain solution B.
[0014] Preferably, step 3) is specifically:
[0015] Solution A and solution B were mixed and ultrasonically oscillated until uniform, and added into a stainless steel autoclave, which was heated at 100°C for 12 hours. The resulting product was washed three times with N,N-dimethylformamide and methanol, respectively, and then dried at 60°C for 12 hours to obtain a defective metal organic framework catalyst.
[0016] Beneficial effects:
[0017] 1) The defective nickel-based MOF catalyst prepared by the present invention does not change the basic skeleton of the parent MOF, but the coordination environment and electronic configuration of the central metal nickel have undergone significant changes. The OER catalytic activity performance of the defective nickel-based MOF catalyst is much better than that of the nickel-based MOF without defects.
[0018] 2) In the defective nickel-based MOF prepared by the present invention, the metal node nickel is a non-precious metal, which reduces the manufacturing cost of the OER catalyst.
[0019] 3) The present invention successfully prepared defective nickel-based MOF, providing a new direction for the modification of MOF materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 XRD diffraction patterns of NiBDC, NiBDC-Fc-0.5 and NiBDC-Fc-1.0 in the examples;
[0021] Figure 2 NiBDC and NiBDC-Fc-1.0 in N 2 TG / DTG curves under N environment; (a) is the TG / DTG curves of NiBDC under N 2 TG / DTG curves of NiBDC-Fc-1.0 under N 2 TG / DTG curve under environment;
[0022] Figure 3 The infrared spectra of NiBDC, NiBDC-Fc-0.5 and NiBDC-Fc-1.0 in the embodiments of the present invention are shown in FIG.
[0023] Figure 4 XPS spectra of NiBDC and NiBDC-Fc-1.0: (a) is the full scan spectrum; (b) is the Ni 2p fine spectrum; (c) is the O1s fine spectrum; (d) is the XPS valence band spectrum;
[0024] Figure 5Figure 1 is a study result of the electrocatalytic OER performance of NiBDC and NiBDC-Fc-x; (a) is the polarization curve of NiBDC, NiBDC-Fc-0.5 and NiBDC-Fc-1.0 in 1M KOH electrolyte (scan rate 10mV / s); (b) is the overpotential bar graph of NiBDC, NiBDC-Fc-0.5 and NiBDC-Fc-1.0; (c) is the overpotential bar graph of NiBDC-Fc-x at 10mA / cm 2 Overpotential bar graph under current density; (d) Tafel curves of NiBDC, NiBDC-Fc-0.5 and NiBDC-Fc-1.0 during the OER process. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is described in detail below through embodiments, but the protection scope of the present invention is not limited to the embodiments.
[0026] Example 1: Synthesis of defective metal organic framework catalysts
[0027] The main raw materials involved in the embodiment are as follows:
[0028]
[0029] 1. Preparation of Metal-Organic Framework Catalyst NiBDC
[0030] Weigh 166 mg, 1 mmol of terephthalic acid and dissolve it in 5 mL of N,N-dimethylformamide, and add 1 mL of 0.4 M NaOH dropwise.
[0031] Weigh 291 mg, 1 mmol of nickel nitrate hexahydrate and dissolve it in 5 mL of N,N-dimethylformamide.
[0032] The above solutions were mixed and ultrasonically vibrated until uniform, and slowly added into a stainless steel autoclave, and the autoclave was heated at 100°C for 12 hours. The obtained product was washed with N,N-dimethylformamide and methanol for 3 times, respectively, and then dried at 60°C for 12 hours. The obtained metal organic framework catalyst was recorded as NiBDC.
[0033] 2. Preparation of defective metal organic framework catalyst NiBDC-Fc-x
[0034] Weigh 166 mg, 1 mmol of terephthalic acid and x mmol of ferrocenecarboxylic acid (x = 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0) and dissolve them in 5 mL of N,N-dimethylformamide, and add 1 mL of 0.4 M NaOH dropwise.
[0035] Weigh 291 mg, 1 mmol of nickel nitrate hexahydrate and dissolve it in 5 mL of N,N-dimethylformamide.
[0036] The two solutions were mixed and ultrasonically oscillated until uniform, and slowly added into a stainless steel autoclave. The autoclave was heated at 100°C for 12 hours. The resulting product was washed three times with N,N-dimethylformamide and methanol, respectively, and then dried at 60°C for 12 hours to obtain a defective metal organic framework catalyst.
[0037] According to the added amount of ferrocenecarboxylic acid x mmol, the obtained defective metal organic framework catalysts were recorded as NiBDC-Fc-0.1, NiBDC-Fc-0.2, NiBDC-Fc-0.3, NiBDC-Fc-0.4, NiBDC-Fc-0.5, NiBDC-Fc-0.6, NiBDC-Fc-0.7, NiBDC-Fc-0.8, NiBDC-Fc-0.9, and NiBDC-Fc-1.0.
[0038] 3. The structural characterization of defective metal organic framework catalysts was tested, and the results are as follows:
[0039] 1) Powder X-ray diffraction (PXRD) test
[0040] Use Cu K α The MOF was characterized by powder X-ray diffractometer with a tube voltage of 40000 V, a current of 100 mA, a scanning range of 5-80 degrees, and a scanning speed of 3 degrees per minute. Figure 1 The XRD spectra of NiBDC, NiBDC-Fc-0.5 and NiBDC-Fc-1.0 prepared at 100°C. It can be seen that at 2θ=8.8°, 15.6°, NiBDC has diffraction peaks, which are basically consistent with the ideal NiBDC crystal data. After the introduction of ferrocenecarboxylic acid, the main peaks of NiBDC-Fc-0.5 and NiBDC-Fc-1.0 are 8.7°, 15.58° and 8.72°, 15.56°, respectively, which are basically consistent with the defect-free NiBDC crystal structure. This shows that NiBDC, NiBDC-Fc-0.5 and NiBDC-Fc-1.0 are isostructural and have very similar topological structures, and the introduction of defect modifiers does not lead to the collapse of the NiBDC structure.
[0041] 2) Thermogravimetric analysis (TGA) test
[0042] Figure 2 (a) and (b) show the 2Thermal weight loss curves of NiBDC and NiBDC-Fc-1.0 in atmosphere. Both NiBDC and NiBDC-Fc-1.0 have high thermal stability. When the temperature is greater than 400°C, the crystal structure of the catalyst gradually collapses. Good thermal stability provides a guarantee for the commercial application of the catalyst. At 100-141°C, NiBDC has a mass loss of about 0.23%, which is caused by the evaporation of water molecules adsorbed in the skeleton. At around 510°C, there is a mass loss caused by the decomposition of the NiBDC structure, and the mass loss is about 36.38%, see Figure 2 Compared with NiBDC, NiBDC-Fc-1.0 has a relatively significant heat loss in the range of 100-400℃, which should be caused by the thermal decomposition of the introduced ferrocenecarboxylic acid, see Figure 2 Middle (b).
[0043] 3) Infrared analysis
[0044] This example uses Fourier transform infrared spectroscopy to further determine more detailed structural changes. Figure 3 As shown, NiBDC (black solid line), NiBDC-Fc-0.5 (red solid line) and NiBDC-Fc-1.0 (blue solid line) at 3600 cm -1 The signal peaks near NiBDC are attributed to the O—H stretching vibration of the carboxyl functional groups of terephthalic acid and ferrocenecarboxylic acid or the O—H stretching vibration of adsorbed water molecules. Compared with NiBDC and NiBDC-Fc-0.5, NiBDC-Fc-1.0 has a peak at 3600 cm -1 The signal peaks near the NiBDC-Fc-0.5 and NiBDC-Fc-1.0 have a stronger pair intensity, indicating that there may be more ferrocenecarboxylic acid molecules in the NiBDC-Fc-1.0 matrix. -1 There is a weak signal peak nearby, which can be attributed to the stretching vibration of the five-membered ring in the ferrocenecarboxylic acid molecule. The above results fully demonstrate that the defect modifier is successfully introduced into the NiBDC matrix in this example.
[0045] 4) X-ray photoelectron spectroscopy (XPS) test
[0046] X-ray photoelectron spectroscopy is an electron energy spectrum based on the photoelectric effect. It uses X-ray photons to excite the inner-shell electrons of atoms on the surface of a substance and performs energy analysis on these electrons. XPS can analyze all elements except H and He. There is less mutual interference between adjacent elements, the element identification is strong, chemical shifts can be observed, and quantitative analysis can be performed. In order to explore the elemental composition and electronic state of NiBDC, NiBDC-Fc-0. and NiBDC-Fc-1.0, this example uses an X-ray photoelectron spectrometer to conduct a detailed investigation of the samples. Figure 4 As shown in the full XPS scan spectrum of NiBDC, characteristic peaks of C (285 eV), O (532 eV) and Ni (855 eV) can be observed in the scan spectrum. Figure 4 As shown in (a), after the defect modifier ferrocenecarboxylic acid was introduced, an obvious Fe (714 eV) element signal appeared in the XPS scanning spectrum of NiBDC-Fc. Figure 4 (a) demonstrates the successful introduction of the defect modifier ferrocenecarboxylic acid into NiBDC. Ni 2p of NiBDC and NiBDC-Fc 3 / 2 It indicates that the Ni cation is Ni 2+ state, see Figure 4 (b) Compared with NiBDC, Ni 2p in NiBDC-Fc 3 / 2 and O1s have higher binding energy and broader peaks, indicating that the introduction of defect modifiers changes the coordination environment of the activation center ( Figure 4 (b), (c)). The electronic structure of the MOF catalyst was studied by XPS valence band spectroscopy. After the introduction of the defect modifier, the energy gap value of NiBDC-Fc shifted to the left by 0.83 eV relative to NiBDC, indicating that the introduction of the defect modifier effectively adjusted the electronic structure of NiBDC.
[0047] Example 2: OER performance of the catalyst prepared in Example
[0048] This example tests the OER performance of NiBDC and NiBDC-Fc-x prepared in Example 1 as catalysts in 1 M KOH solution.
[0049] Test method: Take 2.5 mg of NiBDC and NiBDC-Fc-x and mix them with 2.5 mg of carbon powder respectively, add 950 μL of isopropanol to the mixed powder, ultrasonicate for 90 min, add 50 μL of Nafion again, ultrasonicate for 30 min again to obtain a uniform dispersion, take 10.0 μL of the dispersion and add it to the pretreated glassy carbon electrode, and dry it to obtain the working electrode. The OER performance of the working electrode was tested using the CHI760E electrochemical analyzer of Shanghai Chenhua Instrument Co., Ltd. The electrocatalytic performance of the prepared NiBDC, NiBDC-Fc-0.5, and NiBDC-Fc-1.0 was studied using a three-electrode system at room temperature and in alkaline conditions (the electrolyte was 1 M KOH), and the reference electrode was Hg / Hg 2 Cl 2 The counter electrode was a platinum wire. The OER activity of the catalyst was tested by linear voltammetry with a scan rate of 10 mV / s and a voltage range of 0-0.8 V.
[0050] After the defect modifier was introduced, the changes in the electrocatalytic performance of MOF were observed. Under alkaline conditions (1M KOH), the electrocatalytic performance of the prepared NiBDC, NiBDC-Fc-0.5, and NiBDC-Fc-1.0 was studied in a three-electrode system. NiBDC, NiBDC-Fc-0.5, and NiBDC-Fc-1.0 were loaded on a glassy carbon electrode with a diameter of 5 mm. The loading volume of the uniform dispersion of NiBDC, NiBDC-Fc-0.5, and NiBDC-Fc-1.0 and carbon was 10.0 μL. Figure 5 shown.
[0051] from Figure 5 In (a), it can be seen that the OER curves of NiBDC, NiBDC-Fc-0.5, and NiBDC-Fc-1.0 are significantly different. The curves from NiBDC, NiBDC-Fc-0.5 to NiBDC-Fc-1.0 gradually become steeper, indicating that their OER performances are gradually improved. Figure 5 It can be seen from (c) that the Tafel slopes of NiBDC, NiBDC-Fc-0.5, and NiBDC-Fc-1.0 are 0.175, 0.150, and 0.125, respectively, and the catalytic activity is improved. Figure 5 In (b), it can be seen that the current density is 10mA / cm 2 When the overpotential of NiBDC, NiBDC-Fc-0.5 and NiBDC-Fc-1.0 is 400mV, 319mV and 306mV respectively, the current density is 50mA / cm 2When the overpotential of NiBDC, NiBDC-Fc-0.5 and NiBDC-Fc-1.0 is 516mV, 418mV and 384mV respectively, the current density is 100mA / cm 2 When the overpotential of NiBDC-Fc-0.5 and NiBDC-Fc-1.0 was 546mV and 496mV, respectively, it indicates that the introduction of defect modifier significantly improves the catalytic performance of NiBDC-Fc.
[0052] Keeping other quantities unchanged, changing the addition amount of defect modifier ferrocenecarboxylic acid x (x = 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0 mmol), the polarization curve of NiBDC-Fc-x in KOH electrolyte can be obtained. Figure 5 As shown in (d), the curve of NiBDC-Fc-x gradually becomes steeper as x increases. As the amount of introduced ferrocenecarboxylic acid increases, the OER performance of NiBDC-Fc-x gradually improves, and it is optimal when x = 1.0.
[0053] In summary, the present invention introduces defect modifiers to modify NiBDC, using terephthalic acid, NaOH, Ni(NO 3 ) 2 6H 2 O. Defective MOF (NiBDC-Fc-x) was synthesized using ferrocenecarboxylic acid as raw material. The reaction was carried out at 100°C. The morphological structure and electrochemical performance of NiBDC-Fc-x synthesized with different amounts of ferrocenecarboxylic acid were characterized, and the following conclusions were drawn.
[0054] 1) The present invention adopts a hydrothermal method to prepare NiBDC and NiBDC-Fc-x. XRD characterization shows that the introduction of defect modifiers does not cause damage to the MOF organic framework. Thermogravimetric analysis shows that the amount of MOF mass change changes with temperature, and the mass of each element can be obtained. Through infrared analysis and XPS spectra, it can be clearly found that the Fe element exists in the NiBDC-Fc catalyst introduced with the defect modifier.
[0055] 2) The present invention introduces defect modifiers in an alkaline environment to improve the electrochemical oxygen evolution performance of NiBDC. The amount of the introduced defect modifiers increases from 0 to 1 mmol, and the electrochemical oxygen evolution of the NiBDC-Fc-x generated by them gradually increases, and 1.0 mmol reaches the best performance. At a current density of 10 mA / cm 2 When the overpotential is 306 mV, the performance of NiBDC-Fc-1.0 is much better than that of NiBDC without defects under the same test conditions.
[0056] 3) The present invention intentionally produces NiBDC-Fc with different defect concentrations by introducing different amounts of ferrocenecarboxylic acid, providing a new direction for the modification of MOF materials.
[0057] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes in form and details may be made without departing from the spirit and scope of the present invention.
Claims
1. A method for synthesizing a defective metal organic framework catalyst, characterized in that: The nickel nitrate hexahydrate is reacted with an organic ligand and a defect regulator by a hydrothermal method to obtain a defective metal organic framework catalyst, wherein the defect regulator is ferrocenecarboxylic acid and the organic ligand is terephthalic acid.
2. The synthesis method according to claim 1, characterized in that The molar ratio of the organic ligand to the defect modifier is 1:(0.1-1).
3. The synthesis method according to claim 1, characterized in that Step 1), dissolving terephthalic acid and ferrocenecarboxylic acid in N,N-dimethylformamide, and adding NaOH solution dropwise to obtain solution A; the molar ratio of terephthalic acid to ferrocenecarboxylic acid is 1:(0.1-1); Step 2), dissolving nickel nitrate hexahydrate in N,N-dimethylformamide to obtain solution B; Step 3), solution A and solution B are mixed evenly, added into a stainless steel autoclave, heated for a period of time, and then the obtained product is washed and dried to obtain a defective metal organic framework catalyst.
4. The synthesis method according to claim 3, characterized in that Step 1) is specifically as follows: dissolving terephthalic acid and ferrocenecarboxylic acid in 5 mL of N,N-dimethylformamide, and adding 1 mL of 0.4 M NaOH dropwise thereto to obtain solution A; the terephthalic acid is 1 mmol; Step 2) is specifically as follows: 1 mmol of nickel nitrate hexahydrate is dissolved in 5 mL of N,N-dimethylformamide to obtain solution B.
5. The synthesis method according to claim 3, characterized in that Step 3) is specifically: Solution A and solution B were mixed and ultrasonically oscillated until uniform, and added into a stainless steel autoclave, which was heated at 100°C for 12 hours. The resulting product was washed three times with N,N-dimethylformamide and methanol, respectively, and then dried at 60°C for 12 hours to obtain a defective metal organic framework catalyst.
6. Use of the defective metal organic framework catalyst prepared by the synthesis method according to any one of claims 1 to 5 as an OER catalyst.